Morals in the Digital Age: Building a Moral Digital Society - Ashidqi, Robbi Fadlli Ashidqi; Ihya, Cinta Nur; Purnomo, Halim (Jurnal Studi Islam dan Kemuhammadiyahan (JASIKA), 2025)
The development of technology in the digital era has brought significant changes to human life. However, the rapid advancement of technology that is not aligned with knowledge and the values of Islamic teachings can have a negative impact on society. This issue becomes a concern and challenge in maintaining ethics in the digital era. Method in this researcg use the literature by article or paper from journal, digital publication by search/browse in the searching application. This article discusses the importance of building a morally upright digital society, with a focus on ethics in the use of technology, particularly smartphones. The article presents several efforts that can be implemented to build a morally upright digital society, enabling people to face the digital era equipped with both knowledge and the ethical values taught in Islam. The results of the resaerch show that morality, especially for a Muslim, is how he can position himself in relation to God, society and the surrounding environment.